2014
DOI: 10.4028/www.scientific.net/kem.621.311
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of High Pressure Transients in Water Hydraulic Pipeline Using Matlab/Simulink

Abstract: Based on the continuity equation and the motion equation of fluid dynamics, a mathematical model of high pressure transients in water hydraulic pipeline is presented. In the model, the friction item is consist of steady friction item and dynamic friction item, using the Darcy-Weisbach equation to solve steady viscous friction item and using four exponential terms instead of weighting function to solve dynamic friction item. By finite difference method accompanied with Matlab/Simulink, an example of high pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…By constructing mathematical models of pipeline and load, Li et al 16 concluded that parameters such as pipe length and pipe diameter can affect the stability of hydraulic system. Zhao et al 17 used Matlab/Simulink to analyze the transient state of high-pressure pipeline and simulated the dynamic characteristics of pressure transient. Zhao 18 built the simulation model of trapezoidal and three-inlet and three-return fluid supply pipeline, and concluded that the latter can reduce the pressure loss and improve the column lifting speed.…”
Section: Optimal Tracking Control Of the Coal Mining Face Fluid Suppl...mentioning
confidence: 99%
See 1 more Smart Citation
“…By constructing mathematical models of pipeline and load, Li et al 16 concluded that parameters such as pipe length and pipe diameter can affect the stability of hydraulic system. Zhao et al 17 used Matlab/Simulink to analyze the transient state of high-pressure pipeline and simulated the dynamic characteristics of pressure transient. Zhao 18 built the simulation model of trapezoidal and three-inlet and three-return fluid supply pipeline, and concluded that the latter can reduce the pressure loss and improve the column lifting speed.…”
Section: Optimal Tracking Control Of the Coal Mining Face Fluid Suppl...mentioning
confidence: 99%
“…Remark 1 The adaptive law ( 23) is driven by the variable θ calculated from (22) with the auxiliary variables and . As defined in (17), they can be calculated using the system output X for the regressor O 1 and output vector E 1 . As shown in (21), θ contains information of estimation error W .…”
Section: Adaptive Optimal Control Designmentioning
confidence: 99%